Accessibility of the Curriculum by Learners with Conduct Disorders in Nkayi Rural Primary Schools in Zimbabwe - Siziba Khumbulani; Thomas Musankuleni Kaputa (Utan Kayu Publishing, 2023)
The study sought to find out the challenges and opportunities posed by the current curriculum when including learners with conduct disorders in mainstream primary schools in Nkayi District in Zimbabwe. Using a qualitative approach focusing on a case study design data was generated from Fifteen participants (1 school head, 4 mainstream teachers, and 10 learners with conduct disorder) were purposively selected. All participants were interviewed individually. Theme identification methods were used to analyse data. The findings showed that all students showing signs of conduct disorder were mostly taught by regular class teachers in the mainstream. Despite having mainstream teachers and a specialist teacher, learners with conduct disorders could not perform well in their academic work as all mainstream teachers were not conversant with ways of identifying and managing learners with conduct disorders in primary school. It was revealed that there was a lack of proper guidance and counselling and parental involvement in dealing with learners with conduct disorders. Learners with conduct disorders were socially included but were academically excluded because of lack of measures to manage learners with conduct disorders for them to access the academic curriculum in the primary schools. For learners with conduct disorders to fully access the curriculum, this study recommended that teachers should be fully capacitated to manage learners with conduct disorders, reduced teacher-pupil ratio in primary schools, involve parents in the management of learners with conduct disorders and capacitate school guidance and counsellors.